Overview of Metastasis Locations in Breast Cancer Patients Based on Histopathological Type and Grading in Cut Meutia General Hospital Lhokseumawe in 2020-2021 - Khairunnisa Z; Adi Rizka; R, Afifah Aulia (HM Publisher, 2022)
Breast cancer is the most common type of cancer in women and is one of the most common causes of death. Breast cancer can develop into malignant when the cell invades surrounding tissue or metastasizes (spreads) to other organs of the body. Several examinations can be done to monitor the growth to malignancy of breast cancer, such as histopathology examinations. The purpose of this study is to find out the location of metastasis based on the type and grading of histopathology in breast cancer patients at Cut Meutia Lhokseumawe Hospital in 2020-2021. This study was a descriptive observational study using a cross-sectional design. The study sample was breast cancer patients who had metastases and met the inclusion and exclusion criteria of as many as 36 people. The incidence of breast cancer metastasis mostly occurs at the age of 36-45 (38.9%), the most histopathological type was invasive ductal carcinoma (83.3%), and the most histopathological grading was grade III (52.8%). The most common site of metastases in this study was bone (50%). Invasive ductal carcinoma and invasive lobular carcinoma tend to metastasize to the bone. Grade II tends to metastasize to the bone. While grade III tends to metastasize to the lungs.